Integrating evidence-based nursing teaching in the Child Care and Nursing study subject and in the Pediatric Nursing Practice - Šakalytė, Danguolė; Kriukelytė, Daiva; Indrašienė, Valdonė (Slauga. Mokslas ir praktika, 2023)
Evidence-based nursing is one of the newest paradigms in nursing. Its application means that future nurses need to know how to obtain reliable evidence, to match it with their clinical competence and the needs and values of the patient. Appropriate content for training evidence-based nursing ensures that future nurses have a positive attitude towards evidence-based nursing and its application in child care and nursing. Aim. To validate theoretically and empirically the possibilities of teaching evidence-based nursing in the Child Care and Nursing study subject and in the Pediatric Nursing Practice. A three-phase action research study was conducted and a mixed-methods research approach. Interviews and a questionnaire survey were conducted. Interview data analysed using qualitative content analysis. The questionnaire data were analysed using an independent samples t-test with a significance level of p < 0.05. The participants were 74 students in their second year of study. Results and conclusions. A curriculum of study subject and practice has been developed to teach the steps of evidence-based nursing. The tasks have been developed to enhance students’ learning of evidence-based nursing. Two iterative cycles of action research were carried out to teach the renewed Child Care and Nursing study course and Pediatric Nursing Practice. A student survey was carried out at the end of the training. Students scored highest on skills in disseminating information with colleagues, applying evidence and evaluating performance. Meanwhile, more emphasis should be placed on teaching students to understand the formulation of questions and to critically evaluate evidence.